Towards Understanding the Synergetic Relationship of Data Visualization with Learning Analytics: A Review - Khuzairi N.M.S.; Cob Z.C.; Hilaluddin T. (American Institute of Physics Inc., 2023)
As online learning and the use of learning management systems grows rapidly, large amounts of educational data are made available for learning analytics. Data visualization plays an important role within learning analytics, as it generates complex analysis and data into a visual representation for easy comprehension by the user to support better decision-making among stakeholders (e.g. students, educators, administrators). The purpose of this paper is to review the existing studies to provide an overview of data visualization in learning analytics within the educational communities. First we analyze the use of data visualization and learning analytics purposes in the contexts of its stakeholders. Second, we examine the relationship between data visualization and learning analytics in the development of learning management systems and then we discuss the challenges found. A systematic literature review was conducted based on the research keywords from reputable databases and 62 journal articles published from 2011 to 2021 were identified. The results from this review suggest there is an indispensable synergetic relationship between data visualization and learning analytics for successful learning management systems. Also there is a lack of studies that consider data visualization and learning analytics from the technological theories perspective. 2022 American Institute of Physics Inc.. All rights reserved.